Double Nanoporous Structure with Nanoporous PtFe Embedded in Graphene Nanopores: Highly Efficient Bifunctional Electrocatalysts for Hydrogen Evolution and Oxygen Reduction. Issue 5 (15th December 2016) - Zhong, Xing; Wang, Lei; Zhuang, Zhenzhan; Chen, Xianlang; Zheng, Jian; Zhou, Yulin; Zhuang, Guilin; Li, Xiaonian; Wang, Jianguo
Abstract : Pt‐based alloys are considered the universal choice among electrocatalysts for both hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR). However, improving the electrocatalytic efficiency with the use of minimal amount of Pt is very challenging. A new strategy has been developed to fabricate a "double nanoporous" structure, in which nanoporous PtFe alloy (np‐PtFe) is embedded in nanoporous graphene (NPG), through in situ etching and acid leaching treatments. The np‐PtFe/NPG‐700 served as an effective bifunctional catalyst for both HER and ORR, exhibiting higher activity and stability than 20% Pt/C. Theoretical calculations reveal that the graphene nanopores not only play a vital role in improving the stability of the nanoporous PtFe alloy but also downshift the d‐band center of the PtFe alloy, thus improving the catalytic activity. The double nanoporous structure also provides numerous diffusion channels, which facilitated the mass and charge transport during HER and ORR. Abstract : Double nanoporous structure with nanoporous PtFe embedded in graphene nanopores (np‐PtFe/NPG) is fabricated. The np‐PtFe/NPG‐700 serves as an excellent bifunctional electrocatalysis for both hydrogen evolution reaction and oxygen reduction reaction. Theoretical calculation reveals the possible mechanism for the enhanced catalytic activity. Double nanoporous structure provides diffusion channels to facilitate the mass and charge transport.